Remediation of nitrogen polluted water using Fe–C microelectrolysis and biofiltration under mixotrophic conditions. (October 2020) - Quan, Xiangchun; Zhang, Haifeng; Liu, Hezun; Chen, Liang; Li, Naiyu
Abstract: A hybrid biofilter was established on Fe–C supported carriers aimed to enhance nitrogen removal from polluted water of low Carbon/Nitrogen (C/N) ratio. Effects of organic loadings, hydraulic retention time (HRT), additional electron donor (Fe 2+ ) supplementation and operation mode on the performance of the biofilter were investigated. Results showed that up-flow operation mode was better than down-flow mode in terms of nitrate and total nitrogen (TN) removal at low COD/N. The average removal of NO3 − -N, NH4 + –N and TN attained 83.1%, 84.7% and 81.2%, respectively, under the conditions of influent COD/NO3 − -N = 1.5–3.6, HRT = 10 h and up-flow operation. When the biofilter was operated under autotrophic conditions without organic compounds in influent as electron donors, the biofilter achieved a NO3 − -N removal of 46% and TN removal of 56% depending on the innate electron donors provided by the Fe–C carriers. Supplementation of Fe 2+ in influent further promoted autotrophic denitrifying process, and the removal of NO3 − -N and TN increased to 96.3% and 84.7%, respectively, at the mol ratio of Fe 2+ /NO3 −  = 10 and HRT = 10 h. The microbial community was analyzed for the biofilm samples enriched under heterotrophic and autotrophic conditions. The Fe–C biofilter boosted the growth of a large population of mixotrophic denitrifying bacteria including Gallionella, heterotrophic denitrifying bacteria Denitratisoma, and autotrophic denitrifying bacteria Thiobacillus and Thioalkalispira . On the whole, the biofilter coupled with Fe–C micro-electrolysis provides a novel strategy to treat polluted water of low C/N under both heterotrophic and autotrophic conditions. Highlights: A biofilter coupling Fe–C microelectrolysis was established to remove N. Nitrate was removed by mixotrophic denitrification and chemical reduction. Fe–C biofilter boosted the growth of mixotrophic denitrifying bacteria. Supplementation of Fe 2+ in influent further promoted autotrophic denitrification.